The Effect of Adaptability, Supervision, and Leadership Training on Managerial Performance - Hidayat; Malik, Tajuddin; Bata Ilyas, Gunawan (Cendekiawan Indonesia Timur, 2023)
In educational activities, the principal acts as a leader with duties and functions related to the education progress in the school he leads. Educational leadership policies that empower teachers are essential to building superior and productive teacher performance. The organization can run effectively if the management functions such as planning, organizing, monitoring, and motivation function properly and the supporting elements are available and meet the requirements. This is descriptive qualitative research, in which the data is presented in words and pictures rather than numbers. Researchers can use understanding data collection techniques to collect data where the method shows an abstract. The data analysis is descriptive-analytical, describing the data in words and pictures rather than numbers. Data derived from manuscripts, interviews, field notes, documents, and other sources are then related to shedding light on reality or reality. In qualitative research, data analysis occurs before entering the field, in the area, and after completion. Listening and regular reflection are essential to a leader's growth. The results show that servant leaders develop the ability and commitment to recognize and clearly understand the words conveyed by others. They try to listen attentively to what is said and not said. They discover what's in their heart by listening, which goes beyond trying to beat their inner voice and understand what the body, soul, and mind are communicating.